A machine learning-based approach for data analysis to ascertain suicidal individuals from Social media users - Nahar, Fatiha Binte Kamrun; Afsana, Umme Halima; Chowdhury, Azizul Muktadir; Hasnaen, Maha; Jahan, Sumaya (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.